The Role of Interactive E-books Problem Based Learning to Enhance Higher Order Thinking Skills Ability: Teacher’s Perception - Kusuma, Fiska Fatrisia; Sunyono, Sunyono; Lengkana, Dewi (Jurnal Pendidikan MIPA, 2022)
This study aimed to describe teacher's perception toward usage of interactive e-books based Problem Based Learning (PBL) to Envhance Higher Order Thinking Skills (HOTS). The research was conducted in 50 junior high school science teachers. The method used in this research is a mixed method with Sequential Explanatory Design. The method used in this study is a mixed method with Sequential Explanatory Design. Data is retrieved using questionnaire. Data were analyzed using descriptive analysis. The survey results show that students have a positive perception of interactive e-books based PBL. The results of the analysis of e-books, most eachers have not used interactive e-books with a PBL approach to provide an understanding of science. E-books that have not trained students' HOTS are also included in the low category because teacher has not set strategies, methods, models and lack of knowledge about technology. It can be said that interactive e-book based PBL are needed by teachers and students to improve students’ HOTS.Keywords: teacher perception, interactive e-books, problem-based learning, higher order thinking skills.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp234-243